When the Nile is Contested: A Dynamics of Water Conflicts in the Middle East and the Challenge of Solutions - Dermawan, Windy; Primawanti, Henike; Azmi, Fuad (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2024)
This paper aims to analyse the hydropolitical conflict on the Nile River as a form of struggle for natural water resources by the countries involved in the Middle East, especially Egypt and Ethiopia. The Nile River has strategic value in both political and economic aspects. Many agreements have been made to avoid hydropolitical conflicts on the Nile River both bilaterally and multilaterally, although some have created new problems. The existence of factors that can affect the amount of water in the Nile, population growth, climate change, and the construction of the GERD dam by Ethiopia are new challenges for neighbouring countries regarding the future of water in the Nile and solutions to deal with it. This research uses qualitative methods with data collection through documentation studies, archival studies and internet-based studies. The concepts of conflict and conflict resolution were used as a theoretical framework to unravel the problem. The author found that hydropolitical conflict caused by the struggle over the Nile River is one of the prominent forms of conflict that has the potential to threaten security and peace in the region. Cooperation and the drafting of agreements that are more inclusive and represent the interests of the disputing parties are needed.